IMPACT OF ULTRA-PROCESSED FOODS ON THE QUALITY OF LIFE OF EDUCATION WORKERS: MENTAL AND SEXUAL HEALTH (CIPEEX, 2025)
Ultra-processed foods (UPF) are ready-to-eat industrialized products with little or no whole food, as well as high levels of additives, preservatives, salt, sugars and fats. High consumption of these foods is associated with an increased risk of chronic non-communicable diseases such as obesity, cancer, diabetes, dyslipidemia, as well as mental disorders such as anxiety and depression, resulting in high long-term mortality. All these negative impacts on health can have an impact on sexual health, contributing to a worse outcome. Therefore, the aim of this study was to associate the regular consumption of ultra-processed foods with the sexual health, quality of life and mental health of civil servants from the Federal Network for Professional, Scientific and Technological Education (FNPSTE). This is a cross-sectional epidemiological study, with a quantitative approach, carried out in November 2022. The sample consisted of 1,563 participants, including teachers and administrative technicians in education from all Brazilian regions. An online questionnaire was used to collect sociodemographic data; the WHO Quality of Life Assessment Tool - WHOQOL-100; the Depression, Anxiety and Stress Scale - DASS-21; and the National School Health Survey - PeNSE. The data was analyzed using descriptive statistics, the Chi-square association test and Poisson regression. The measure of effect was the prevalence ratio with its respective 95% confidence intervals (CI). Regular consumption (RC) is defined as ≥ 5 days a week. All the analyses were carried out using the Statistical Package for the Social Sciences (SPSS) version 23.0, with α = 0.05. The RC of UPF was found in 15.4% of men and 13.9% of women; in single individuals (15.1%); in the ≤35 age group (17.5%); with a Master's degree (20.7%); teachers (14.9%); southern region (17.4%); with up to 10 years' service (15.8%); urban dwellers (16.6%). When related to Quality of Life, RC was associated with the physical (p = 0.006), psychological (p lt; 0.001), social (p = 0.004), environmental (p = 0.005) and total score (p lt; 0.001) domains. In relation to Mental Health, RC was associated with stress, anxiety and depression (p lt; 0.001). When associated with the sexual evaluation questions 'satisfied with sexual needs', 'satisfaction with sex life' and 'general evaluation of sex life', the worst outcome (1 and 2 on the Likert scale) was associated with high consumption of UPF (p lt; 0.001). Thus, regular consumption of UPF has a negative impact on the health of FNPSTE employees, damaging their quality of life, mental health and sexual health. Reducing UPF consumption and adopting healthy food alternatives are recommended to improve general well-being.
Keywords: mental health; sexual health; quality of life; ultra-processed food